2014
DOI: 10.1144/sp398.7
|View full text |Cite
|
Sign up to set email alerts
|

Physical characteristics of tephra layers in the deep sea realm: the Campanian Ignimbrite eruption

Abstract: Tephra deposits in the deep sea can survive undisturbed for long periods of time and, on regional scales, tend to be much better preserved than their subaerial counterparts. In this study, grain size distributions and thicknesses of tephra deposits from the Campanian Ignimbrite (CI) eruption (39 000 yr BP; magnitude c. 7.7) preserved in thirty-three deep sea cores are analysed to infer key eruption parameters. Distal deep sea tephra thickness data show an exponential decrease with distance from source. Such tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 72 publications
(103 reference statements)
7
67
0
Order By: Relevance
“…It was accompanied by a huge volcano-tectonic collapse, giving birth to the Campi Flegrei caldera (CFc; Rosi and Sbrana, 1987;Perrotta et al, 2006;Scarpati et al, 2013). The CI plinian eruption emplaced a large volume of pyroclastic fall and pyroclastic density current products, which resulted in a very complex sequence in proximal, medial and distal outcrops [e.g., Barberi et al (1978);Di Girolamo et al (1984); Rosi and Sbrana (1987);Fisher et al (1993); Scarpati (1994, 2003); Orsi et al (1996); Rosi et al (1996Rosi et al ( , 1999; Cappelletti et al (2003); Perrotta et al (2006); Fedele et al (2008); Perrotta (2012, 2016); Engwell et al (2014); Scarpati et al (2015aScarpati et al ( , 2015b; Sparice (2015)]. …”
Section: The Campanian Ignimbrite Eruptionmentioning
confidence: 99%
“…It was accompanied by a huge volcano-tectonic collapse, giving birth to the Campi Flegrei caldera (CFc; Rosi and Sbrana, 1987;Perrotta et al, 2006;Scarpati et al, 2013). The CI plinian eruption emplaced a large volume of pyroclastic fall and pyroclastic density current products, which resulted in a very complex sequence in proximal, medial and distal outcrops [e.g., Barberi et al (1978);Di Girolamo et al (1984); Rosi and Sbrana (1987);Fisher et al (1993); Scarpati (1994, 2003); Orsi et al (1996); Rosi et al (1996Rosi et al ( , 1999; Cappelletti et al (2003); Perrotta et al (2006); Fedele et al (2008); Perrotta (2012, 2016); Engwell et al (2014); Scarpati et al (2015aScarpati et al ( , 2015b; Sparice (2015)]. …”
Section: The Campanian Ignimbrite Eruptionmentioning
confidence: 99%
“…Such processes may be particularly relevant within active volcanic arc environments, where water depths are shallower than in ocean basins and where complex topography may develop. For example, tephra fallout deposits from the Campanian Ignimbrite, in the Mediterranean Sea, suggests tephra thickness varies according to the surrounding bathymetry (Engwell et al, 2014), and because submarine flows are commonly channelized in depressions, fallout tephras are more likely to survive erosion when they are emplaced on bathymetric highs. In less dynamic environments tephra fallout deposits in marine sediments are commonly normally-graded as they reflect the different sinking velocities of the different eruptive particles through the water column until they reach the ocean floor (Manville and Wilson, 2004).…”
Section: Tephra Fallout Depositsmentioning
confidence: 99%
“…Given that tephra horizons are regionally better preserved in marine environments than in subaerial ones (Engwell et al 2014), we decided to analyse in detail tephra layers in marine cores recovered during the last 30 years by Italian Antarctic Research Program (PNRA). We report here the results of tephrostratigraphic and geochemical studies on eight tephra beds identified in marine sediment sequences from Ross Sea gravity cores.…”
Section: Introductionmentioning
confidence: 99%